2016
DOI: 10.1055/s-0042-121366
|View full text |Cite
|
Sign up to set email alerts
|

PKA and Apicomplexan Parasite Diseases

Abstract: The cAMP-dependent protein kinase PKA is a well-characterized member of the serine-threonine protein AGC kinase family and is the effector kinase of cAMP signaling. As such, PKA is involved in the control of a wide variety of cellular processes including metabolism, cell growth, gene expression and apoptosis. cAMP-dependent PKA signaling pathways play important roles during infection and virulence of various pathogens. Since fluxes in cAMP are involved in multiple intracellular functions, a variety of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Little is known about PKAc1 and its substrates in T. gondii . In contrast, more is known about the contribution of PfPKA in P. falciparum physiology (Haidar et al , ). Notably, PfPKAc was reported to regulate host erythrocyte invasion and the proliferation of merozoites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about PKAc1 and its substrates in T. gondii . In contrast, more is known about the contribution of PfPKA in P. falciparum physiology (Haidar et al , ). Notably, PfPKAc was reported to regulate host erythrocyte invasion and the proliferation of merozoites.…”
Section: Discussionmentioning
confidence: 99%
“…In T. gondii, four putative adenylyl cyclases (ACs) (Mueller et al, 2016) and 18 cyclic nucleotide phosphodiesterases (PDEs) (Howard et al, 2015) have been identified but have not been functionally characterised yet. The role of PKA in Apicomplexa has been best studied in malaria parasites (Haidar et al, 2016). In Plasmodium falciparum asexual erythrocytic stages, PfPKAc was shown to phosphorylate the apical membrane antigen 1 (AMA1), a key protein required for merozoite invasion (Leykauf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…AKAP8 and the neighboring AKAP8L (deleted in nine out of 12 of the reported cases) was already pointed out in association with palatogenesis defects (Cao et al., ; Yang, Mahaffey, Bérubé, & Frankel, ) and with the regulation of head size (Nebel et al., ). Furthermore, they were previously highlighted for their role during infection and virulence of various pathogens (Haidar, Ramdani, Kennedy, & Langsley, ). These observations strongly support AKAP8 and/or AKAP8L deletion as potentially associated with palatogenesis defects, microcephalia, and recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
“…AGC kinase represents a category conserved kinases among eukaryotic genomes, including cyclic AMP [cAMP]-dependent protein kinase 1 (protein kinase A), cGMP-dependent protein kinase (PKG) and protein kinase C, which served various physiological functions, such as cell growth, metabolism, differentiation, and cell death [54]. This kinase was widely expressed in Apicomplexan parasites and contribute to the pathogenesis of parasites [55]. Our data revealed that AGC kinase of sporulated oocyst of T. gondii had regulatory roles in nucleotide binding, ATP binding, metabolic process, protein serine/threonine kinase activity and phosphorylation, indicating the important role of AGC kinase in the biology of T. gondii sporulated oocysts.…”
Section: Kinase-protein Interactionsmentioning
confidence: 99%